2017
DOI: 10.5005/jp-journals-10024-2188
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Marginal Adaptation and Sealing Ability of Root Canal Sealers: An in vitro Study

Abstract: Aim: This study aims to compare the marginal adaptation and sealing ability [mineral trioxide aggregate (MTA)-Fillapex, AH Plus, Endofill sealers] of root canal sealers. Materials and methods:In the present study, the inclusion criteria include 45 single-rooted extracted mandibular premolar teeth, with single canal and complete root formation. The sectioning of the samples was done at the cementoenamel junction using a low-speed diamond disc.Step-back technique was used to prepare root canals manually. The MTA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 13 publications
1
6
0
Order By: Relevance
“…[ 13 ] reported that marginal adaptation was less in all groups based on SEM images in the apical part compared to the middle and coronal parts. Remy et al ,[ 14 ] by evaluation the AH plus sealer, also reported that the marginal adaptation of the apical region was significantly lower than the coronal region. In the present study, it was observed that the depth of tubular penetration was not affected by the filling method; however, it was significantly higher in the use of bioceramic sealer than epoxy resin ( P < 0.001).…”
Section: Discussionmentioning
confidence: 99%
“…[ 13 ] reported that marginal adaptation was less in all groups based on SEM images in the apical part compared to the middle and coronal parts. Remy et al ,[ 14 ] by evaluation the AH plus sealer, also reported that the marginal adaptation of the apical region was significantly lower than the coronal region. In the present study, it was observed that the depth of tubular penetration was not affected by the filling method; however, it was significantly higher in the use of bioceramic sealer than epoxy resin ( P < 0.001).…”
Section: Discussionmentioning
confidence: 99%
“…The adaptation to root canal walls was evaluated using the marginal adaptation, interfacial gaps and void volume in cubic millimetres with mean percentages. The marginal adaptation [ 31 , 48 ] and interfacial gaps [ 39 , 53 , 55 ] were assessed using the Scanning Electron Microscope whereas void volume [ 30 , 41 , 42 , 47 , 51 ] was assessed by Micro-computed Tomography. Kim et al [ 30 ] stated that the voids in the root canal obturation might weaken the filling quality and serve as a hub for microbes by transporting contaminants along the root canal system.…”
Section: Discussionmentioning
confidence: 99%
“…Various studies reported that RBS could penetrate deep into the dentinal tubules due to the flowability, long setting time, and provide long-term dimensional stability [ 48 , 53 , 57 , 58 ]. Germain et al [ 41 ] suggested that EndoSequence (CSBs) reduced film thickness, improved flow and hardening on contact with moisture within the root dentine.…”
Section: Discussionmentioning
confidence: 99%
“…Endodontic sealers have a key role in sealing the root canal system, entombing the residual bacteria, and filling the irregularities in the prepared canal system [13]. The adhesion between the root canal dentin and GP is important in preventing microleakage, which can be attained through the use of different sealers [14]. Therefore, sealers have a great effect on the sealing of the canal space and the success of treatment.…”
Section: Discussionmentioning
confidence: 99%